IMPLEMENTASI PERATURAN DAERAH PROVINSI RIAU NOMOR 12 TAHUN 2002 TENTANG PEMBINAAN DAN PENGAWASAN PENYALURAN BAHAN BAKAR MINYAK OLEH PEMERINTAH KOTA PEKANBARU - Vera Magdalena Siahaan; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Fuel is a vital need for the community, this can be seen from the high level ofpublic demand for means of transportation, currently transportation is no longer aluxury item but a basic need. in everyday life the use of fuel both in industry andtransportation is increasing. With increasing demand, fuel is not supported bynatural resources and continues to decline, therefore management must be carriedout as optimally as possible. In view of this, to ensure the safety and availability offuel, it is necessary to carry out supervision. In this case, the central governmentthrough representatives of each region or local government, namely the PekanbaruCity Industry and Trade Service, supervises the distribution of fuel in PekanbaruCity. The Department of Industry and Trade of Pekanbaru City is the agencyresponsible for the technical implementation of guidance and supervision of thedistribution of fuel in accordance with regional regulation Riau Province Number 12of 2002 concerning guidance and supervision of the distribution of fuel. The practiceof selling retail fuel oil is prohibited by PT. Pertamina as the main distributor.However, judging from the facts on the ground, there are still many people who dothis by buying fuel oil using jerry cans, purchasing in this way is clearly prohibitedand regulated in the regional regulation of Riau Province Number 12 of 2002concerning guidance and supervision of the distribution of fuel to Article 6paragraph 1